Analisis Faktor-Faktor Yang Mempengaruhi Harga Saham Syariah Pada Perusahaan Infrastruktur Di Indonesia Tahun 2019-2021 - Siti Muyasaroh; Mahmudatus Sa'diyah (Fakultas Ekonomi dan Bisnis Universitas Islam Nahdlatul Ulama Jepara, 2023)
Knowledge about choosing the right sharia stock is knowledge that must be owned by every investor. This aims to be able to get benefits and also be able to minimize risks. Knowledge of economic conditions and financial performance in a particular company's shares is one of the benchmarks for determining investment decisions. This study aims to determine the partial effect of the exchange rate, gross domestic product (GDP), return on assets (ROA), return on equity (ROE) and debt to equity ratio (DER) on Islamic stock prices in infrastructure companies in Indonesia in the 2019- 2020. The population in this study are 35 infrastructure companies listed on the Indonesia Stock Exchange (IDX). The sampling technique was carried out by purposive sampling technique and obtained 21 companies as research samples. The observation period is 12 quarters, namely in 2019-2021. So the unit of analysis obtained is 252 after the outliers become 215. The research variable consists of the dependent variable, namely the stock price (Y), the independent variable is the exchange rate (X1), gross domestic product (GDP) ) (X2), return on assets (ROA)(X3), return on equity (ROE)(X4), debt to equity ratio(DER)(X5). Based on the results of multiple linear regression analysis, it can be seen that the exchange rate, GDP, ROA, ROE and DER simultaneously have no effect on Islamic stock prices in infrastructure companies for the 2019-2021 period. Partially, the exchange rate variables, GDP and DER have a positive effect on Islamic stock prices in infrastructure companies for the 2019-2021 period, while the ROA and ROE variables have a negative effect on Islamic stock prices in infrastructure companies for the 2019-2021 period.